If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+65=10x+35
We move all terms to the left:
5x+65-(10x+35)=0
We get rid of parentheses
5x-10x-35+65=0
We add all the numbers together, and all the variables
-5x+30=0
We move all terms containing x to the left, all other terms to the right
-5x=-30
x=-30/-5
x=+6
| (3x+11)°=(2x+4)° | | 7=5–2k | | -50c-c=5c-2 | | 2.3(c-11)=16.1 | | -17+7k=10-8(-9-5k | | 4.8(x-2.5)=-(9.6 | | 0.5x-2.5=3 | | 0.05x-0.1x+0.06=0.04x+2.22 | | 2x+6/2=10 | | |3+x|=−3 | | 289=64+(y+6)^2 | | 445p+145=2400 | | 28= 7x | | Y2+12y-225=0 | | 0.08(2.50t)+5=13.80 | | 5(x+2)-2x=18+3 | | 124=10y | | 9|1+3p|-8=-26 | | 2(3-8n)=-2(8n+3) | | 8(x+5)+9=49 | | -9x=85 | | 13x-7=7x+13 | | (4x+20)=(2x-5) | | (6x-8)=(4x+10) | | x^-4x-200=0 | | x=√20−x | | x^2-6x-667=0 | | 12(x-3)+18=6(2x-9) | | 5x+8/4=-3 | | 15=9-2y | | 5x^2-1=-20 | | 1-x+2x=1.4 |